Pengaruh Reputasi Kantor Akuntan Publik, Umur Perusahaan, Dan Solvabilitas Terhadap Audit Delay - Rahmawati, Riris Indah; Widati, Listyorini Wahyu (Universitas Gorontalo, 2024)
This research was conducted to find out and analyze whether during the Covid-19 pandemic audit delay was influenced by KAP reputation, company age and solvency. This test was carried out on manufacturing companies in the consumer goods industry sector listed on the Indonesian Stock Exchange (BEI) for the period 2020 to 2022. A total of 61 sample companies used in this research were obtained using the 'purposive sampling' method, the data was tested using the technique multiple regression analysis processed with SPSS version 25 software. The results of this research can be concluded that only the Solvency variable does not have a significant effect on Audit Delay.